Two Blizzards, or Authors of Speculative Fiction Write for Young Adults. (1st October 2016) - Zarubina, Dar'ia
Abstract : Dar'ia Zarubina begins with some examples of successful recent fantasy writing for young adults, then zooms in on works by two authors, Dmitrii Kazakov's Moscow Blizzard and Nik Perumov's Molly from North York . Zarubina outlines the plot and style of each work and its relationship to fantasy or steampunk. She concludes that both works are worth giving to young readers, though Kazakov's is better suited to independent reading while Perumov's would be best read by a parent and child together.